The Use of Graph Method and Simplex Method in Optimizing the Production of Teh Rantai Mas Black Tea in CV. Wijaya Mandiri Kreongan Patrang Jember - Fendi Setiawan; Fury Styo Siskawati (Universitas Islam Jember, 2018)
In general, prduction planning in the company still uses a matter of approximately time and production materials alone, so that the processing time and production results are not optimal even though the target has been determined. Based on the results of interview researchers with production managers working in CV. Wijaya Mandiri obtained information that the workforce that produces is still confused with the planning that has been made so that the employment is not maximal in the production process resulted in the production is not optimal. Respondents in this research as much as 6 labor. As for data collection techniques using the method of documentation, interviews, and observation. Based on the conditions in the company, decision makers are faced with conflicting issues between the goals the company wants to achieve with all the limited resources. Therefore with mnggunakan production planning with graphical methods and meode simplek can be achieved optimal production results. The use of graphical methods and simplek methods is a method that is needed to achieve a goal that is best and optimal in producing black tea chain mas. From a variety of many obstacles that exist both these methods become the solution in the next production planning. Keywords: graphik methode and simplek method